Telehealth and Its Prospective for Improving Serious Mental Illness Conditions: A Scoping Review - Widianti, Efri; Suryani, Suryani; Sunjaya, Deni K.; Haroen, Hartiah; Nuraeni, Aan; Kurniawan, Kurniawan (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Health care services ought to be continued for people with serious mental illness (SMI), despite the pandemic events. These efforts help prevent recurrences of any of these medical conditions through the use of telehealth techniques. AIM: The aim of this article is to evaluate the application of telehealth among SMI patients. METHODS: This study used a scoping review framework methodology based on the report by Arksey and O’Malley. A comprehensive literature search was carried out to identify precise studies, and vigorous criteria were employed to select the revelant papers. The search was conducted in several databases, including PubMed, CINAHL (EBSCO), and Science Direct. Subsequently, the data collected were extracted by two independent reviewers, synthesized and presented in the table and narrative format. RESULTS: A total of 13 studies were identified in the search selection process based on the review objectives, and 5 of these studies were randomized control trials (RCT), while 8 used varied research designs. CONCLUSION: Based on the results of the scoping review, telehealth services were concluded to be suitable for helping people with SMI obtain the required mental health services.